Eindexamen. - Soons, Caroline; Elbers, Dennis; AKV St. Joost, Breda; Akademie voor Kunst en Vormgeving, 's-Hertogenbosch ('s Hertogenbosch : AKV/St. Joost, Avans Hogeschool, 2006)
van de Ven, Aldwin ; Osipenkov, Alexander ; Verwegen, Amika ; Berghmans, Andrea ; van den Hurk, Anke ; van Iersel, Anke ; Slingerland, Anne ; Borremans, Annika ; Voermans, Aram ; Colder, Arte ; Thoben, Avelien ; et al.
AKV St. Joost in Breda en 's-Hertogenbosch, 1 t.e.m. 5 juli 2006
kunstcatalogus